2020
DOI: 10.1161/circinterventions.119.008445
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Anomalous Aortic Origin of a Coronary Artery Following a Prospective Standardized Approach

Abstract: Background: Anomalous aortic origin of a coronary artery (CA) is the second leading cause of sudden cardiac death in young athletes. Management is controversial and longitudinal follow-up data are sparse. We aim to evaluate outcomes in a prospective study of anomalous aortic origin of CA patients following a standardized algorithm. Methods: Patients with anomalous aortic origin of a CA were followed prospectively from December 2012 to April 2017. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 35 publications
1
67
0
Order By: Relevance
“…Competitive athletes at the middle school (ages 11-13), high school including premiere/select level (ages 14-18), college (ages 19-23), semiprofessional and professional levels (ages [24][25][26][27][28][29] who experienced SCA/D were included. A competitive athlete was defined as an individual at least 11 years of age involved in regular training in an organised individual or team sport with an emphasis on competition and performance.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Competitive athletes at the middle school (ages 11-13), high school including premiere/select level (ages 14-18), college (ages 19-23), semiprofessional and professional levels (ages [24][25][26][27][28][29] who experienced SCA/D were included. A competitive athlete was defined as an individual at least 11 years of age involved in regular training in an organised individual or team sport with an emphasis on competition and performance.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…5 It has been adopted in children with coronary artery anomaly and ischemia, in whom the risk of surgical intervention outweighs the Submitted April 21, 2020; Accepted August 07, 2020. benefit, such as in this case. 6 Although withholding the b-blocker for 24 hours might not have allowed for a complete assessment of the treatment efficacy, it may not have eliminated the many immediate and long-term potential benefits that b-blockade has on the affected myocardium. Further follow-up is necessary to understand the natural history of this rare anomaly, the potential effects of b-blockade, and which patients would benefit from surgery versus b-blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Farooqi et al reported recommendations for CT imaging and a 3D digital model for evaluation of such anomalies [8]. Similarly, other investigators have advocated for a multispecialty discussion as Heart Team approach between interventional cardiologist and cardiothoracic surgeons [9].…”
Section: Discussionmentioning
confidence: 99%